Article Commentary: Grief and Palliative Care: Mutuality. (January 2013) - Moon, Paul J.
Grief and palliative care are interrelated and perhaps mutually inclusive. Conceptually and practically, grief intimately relates to palliative care, as both domains regard the phenomena of loss, suffering, and a desire for abatement of pain burden. Moreover, the notions of palliative care and grief may be construed as being mutually inclusive in terms of one cueing the other. As such, the discussions in this article will center on the conceptualizations of the mutuality between grief and palliative care related to end-of-life circumstances. Specifically, the complementarity of grief and palliative care, as well as a controvertible view thereof, will be considered.